On the context-dependency of inequality aversion: Experimental evidence and a stylized model - Agnes Bäker; Werner Güth; Kerstin Pull; Manfred Stadler (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We consider three-person envy games with a proposer, a responder, and a dummy player. In this class of games, the proposer, rather than allocating a constant pie, chooses the pie size which the responder can then accept or reject while the dummy player can only refuse his own share. While the agreement payoffs for the responder and the dummy are exogenously given, the proposer acts as the residual claimant who - in case of responder acceptance - receives whatever is left after the two exogenously given agreement payoffs have been deducted from the pie. Consistent with earlier findings from three-person generosity games, we find inequality aversion to be strongly context-dependent and affected by the (in)equality of exogenously given agreement payoffs. Motivated by these findings, we present a stylized model on context-dependent inequality aversion that accounts for the observed effects.
Keywords: C72; C91; D63; 330; Experimental economics; envy game; Nichtkooperatives Spiel; Gerechtigkeit; Test